A simple approach to determine the best threshold value for automatic image thresholding - Abdul Halim, Ismail (IEEE Conference Publications, 2014)
Proceeding of The International Conference on Signal and Image Processing Applications, (ICSIPA09 2009) at Kuala Lumpur, Malaysia on 18 November 2009 through19 November 2009. Link to publisher's homepage at http://ezproxy.unimap.edu.my:2080/Xplore/dynhome.jsp